A via média: política e religião em Rousseau - Araujo, Wagner Cipriano (2010)
This study aims at presenting the position in the work of Rousseau regarding the political implications of religion in the political actions of people. This presentation will be made by examining the texts of the author in which one can find a specific discussion on the topic. To reach the goal of this study, the first topic which is dealt with is the political and religious relationship amongst ancient civilizations; then one discusses the criticisms made by Rousseau to Christianity as a political form dissolved in national religions. Finally, one presents the issues proposed by the author in order to solve the contradictions presented by religious rules cited. Rousseau called his proposed solution civil religion